2004
DOI: 10.1177/107769900408100310
|View full text |Cite
|
Sign up to set email alerts
|

Wag the Blog: How Reliance on Traditional Media and the Internet Influence Credibility Perceptions of Weblogs Among Blog Users

Abstract: This study surveyed Weblog users online to investigate how credible they view blogs as compared to traditional media as well as other online sources. This study also explores the degree to which reliance on Weblogs as well as traditional and online media sources predicts credibility of Weblogs after controlling for demographic and political factors. Weblog users judged blogs as highly credible—more credible than traditional sources. They did, however, rate traditional sources as moderately credible. Weblog use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
324
0
16

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(371 citation statements)
references
References 17 publications
(1 reference statement)
15
324
0
16
Order By: Relevance
“…Blogs, on the other hand, which represent a popular source of social media news information, are often criticized for a lack of the journalistic ethics and standards of more traditional news sources (Johnson & Kaye, 2004). Thus, like health information, online social information about news may be perceived to be less credible than social information about products, which may benefit from effects of aggregation and posts from consumers who are motivated to truthfully share their experience (Resnick, Zeckhauser, Friedman, & Kuwabara, 2000).…”
Section: Social Media Self-efficacy and Information Evaluationmentioning
confidence: 99%
“…Blogs, on the other hand, which represent a popular source of social media news information, are often criticized for a lack of the journalistic ethics and standards of more traditional news sources (Johnson & Kaye, 2004). Thus, like health information, online social information about news may be perceived to be less credible than social information about products, which may benefit from effects of aggregation and posts from consumers who are motivated to truthfully share their experience (Resnick, Zeckhauser, Friedman, & Kuwabara, 2000).…”
Section: Social Media Self-efficacy and Information Evaluationmentioning
confidence: 99%
“…This begs the question why? The answer probably lies in the need to consume tourism products before an evaluation can take place (Dellaert 2000; Rabanser and Ricci 2005;Senecal and Nantal 2004).So online reviews and word of mouth recommendations are a growing and important information source because of the perceived independence of the message source (Gitleson and Kerstetter 1994;Crotts 1999;Dellarocas 2003;Johnson and Kayne 2003;HennigThurau et al 2004;Pan et al 2007;Litvin et al 2007). A recent UK survey found consumers trusted more sites with reviews than professional guides and travel agencies (eMarketer 2007).…”
Section: Internet Applications For Tourismmentioning
confidence: 99%
“…In this sense, several researches showed that citizens perceive social media as a credible source of information, free from the organizational, marketing and economic imperatives faced by traditional journalism (Banning & Sweetser, 2007;Johnson & Kaye, 2004;Kiousis, 2001). …”
Section: Social Media Use and Gatekeeper Perceptionsmentioning
confidence: 99%